Biosafty Evaluation of “Makann” A Bi-herbal Formulation on Female Mice: Kidney and Liver - Itemire, Anne Oghenekevwe; Idu, MacDonald; Enitome, Bafor Evi; Eze, Gerald Ikechi; Gabriel, Benjamin Ogunma (African Journal of Biochemistry and Molecular Biology Research, 2025)
This study evaluated the biosafety of “Makann”, a bi-herbal formulation (Garcinia kola and Carica papaya), on the kidneys and liver of female mice. The collected, washed, shade-dried and processed plant extract (the biherbal formulation) was administered in various groups of female mice at 2 g/kg as a single dose for 24 hours and 14 days, and 14 days daily dose, focusing on body weight, temperature, haematological parameters, organ weight, and histology of the organs using standard analytical methods. The results indicated the biherbal formulated extract at 2 g/kg had no significant difference in the body weight and temperature of the treated animals across single doses of 24 hr and 14 days and 14 daily doses when compared with the control. There was a significant increase in white blood cell count, lymphocyte count, red blood cell count, hemoglobin level, and mean corpuscle hemoglobin concentration in the 24-hr single-dose treated group. Platelet count was significantly increased in all treatment groups compared with the control (p<0.05). The effects of the biherbal extract showed no significant difference in organ weights (liver and kidney) in single doses of 24 hr and 14 days, and daily doses of 14 days when compared with the control groups (p<0.05). The histopathological evaluation of the understudied vital organs revealed no lesions or signs of hepatorenal toxicity across the treatment groups when compared with the control. The insignificant toxicity observed in the biherbal formulation across the studied parameters suggested that the biherbal formulation may exhibit less or no toxicity at the studied dose of 2000 mg/kg. In conclusion, the biherbal formulation may be used at 2 g/kg for safety purposes; further studies on its safety at long-term and other dose administrations should be carried out.